The role of inter-religious dialogue in promoting Islamic education to the Europeans - Shehu, Fatmir Mehdi (Zes Rokman Resources, 2018)
This study investigates the crucial role played by inter-religious dialogue in promoting proper Islamic education to the Europeans. Its goal is to provide a better understanding of Islam and its teachings through proper Islamic education in order to shift the views of Europeans on Islam and Muslims from hostility and enmity to mutual respect and friendliness. The friendly engagement between Muslims and Europeans is very important as it firstly, provides better understanding of Islam, secondly, improves the educational network used by Muslims in their communication of Islamic teachings to their European fellows, thirdly, corrects the diverse interpretations of Islam by European Muslim community (based on their nationalities, cultures, and customs), and the European media (presents Islam and Muslims with stories focused exclusively on hatred, war-making, and devastation). This paper will start with a brief introduction on the Europeans and their religious identity. Then, the main discussion will focus on: (1) what is inter-religious dialogue, Islamic education, religious identity, and their relationship? (2) why inter-religious dialogue is an important means for the promotion of Islamic education to the Europeans (looking at the situation of European Muslims, their relationship with others, and contemporary issues)?, and (3) how inter-religious dialogue promotes Islamic education (discussing themes addressed in inter-religious dialogue activities, establishment of teaching modules, educational centers and institutions, where Islamic education is taught to the Europeans in a dialogue form)? Descriptive and analytical methods will be employed by the researcher with the intention to provide findings that will serve as solid solutions for the proper understanding and interpretation of Islamic tenets through an appropriate Islamic education promoted by inter-religious dialogue.